Mitogenomes of Two Phallus Mushroom Species Reveal Gene Rearrangement, Intron Dynamics, and Basidiomycete Phylogeny - Chen, Cheng; Wang, Jian; Li, Qiang; Fu, Rongtao; Jin, Xin; Huang, Wenli; Lu, Daihua (Frontiers in Microbiology, 2020)
Phallus indusiatus and Phallus echinovolvatus are edible bamboo mushrooms with pharmacological properties. We sequenced, assembled, annotated, and compared the mitogenomes of these species. Both mitogenomes were composed of circular DNA molecules, with sizes of 89,139 bp and 50,098 bp, respectively. Introns were the most important factor in mitogenome size variation within the genus Phallus. Phallus indusiatus, P. echinovolvatus, and Turbinellus floccosus in the subclass Phallomycetidae have conservative gene arrangements. Large-scale gene rearrangements were observed in species representing 42 different genera of Basidiomycetes. A variety of intron position classes were found in the 44 Basidiomycete species analyzed. A novel group II intron from the P. indusiatus mitogenome was compared with other fungus species containing the same intron, and we demonstrated that the insertion sites of the intron had a base preference. Phylogenetic analyses based on combined gene datasets yielded well-supported Bayesian posterior probability (BPP = 1) topologies. This indicated that mitochondrial genes are reliable molecular markers for analyzing the phylogenetic relationships of the Basidiomycetes. This is the first study of the mitogenome of the genus Phallus, and it increases our understanding of the population genetics and evolution of bamboo mushrooms and related species.